Bond strength of universal adhesive applied to dry and wet dentin: one-year in vitro evaluation - Leite, Maria Luísa de Alencar e Silva (2020)
Aim: This study evaluated the influence of dentin wettability on the immediate and extended microtensile bond strength (mTBS) of a universal adhesive system used in the etch-and-rinse strategy. Methods: Twenty human third molars were selected and divided into four groups according to the adhesive system and dentin wettability. The mTBS values of each group were registered 24 h and one year after adhesive system application and resin composite block build-up (n=30). Data were analyzed by the t-test (p<0.05). Results: When both adhesive systems were compared, there was no statistically significant difference when they were applied following wet bonding (p>0.05). However, the dry bonding reduced μTBS values of the Adper Single Bond 2 adhesive (p<0.05). Regarding storage time, both groups presented similar μTBS values at 24 h and one year (p>0.05). Conclusions: Therefore, the Scotchbond Universal Adhesive can be applied to dry or wet dentin without compromising the etch-and-rinse bonding quality and the durability of the restorations.